Assessment of Salt Tolerance in Transgenic Potato Carrying AtNHX1 Gene. Issue 6 (1st November 2013) - Wang, Li; Zhang, Junlian; Wang, Di; Zhang, Jinwen; Cui, Yansen; Liu, Yuhui; Yang, Hongyu; Binyu,
ABSTRACT: Salt tolerance can be assessed with plant morphological and physiological traits. This study evaluated the salt tolerance of eight transgenic potato ( Solanum tuberosum L.) lines using an integrated evaluation index where plant height, leaf area expansion rate, survival rate, and tuber yield were integrated. We hypothesized that (i) the integration of several plant growth traits produced a comprehensive evaluation of salt tolerance, and (ii) the level of salt tolerance in potato was also related to their physiological responses such as chlorophyll and proline contents. A greenhouse study was conducted at Gansu Agricultural University in 2011. Transgenic potato lines carrying AtNHX1 gene expressed significantly higher levels of salt tolerance than the nontransgenic check. The integrated evaluation index showed that the NG‐5 transgenic line had a salt‐tolerance level 46 times that of the check. The check plants had a lower tuber yield when NaCl concentration was 3.3 g L −1 and more than one‐half of the plants died when NaCl concentration was 6.5 g L −1 . The thresholds ranged between 3.7 and 6.8 g L −1 and the half‐lethal (LD50 ) NaCl concentration varied from 8.7 to 14.6 g L −1 for transgenic lines. By Day 40 after salt‐stress challenges at 9 g L −1 NaCl, total chlorophyll content decreased 32% in the check but by an average of 14% in the transgenic lines, whereas proline content in the check was 2.5 times those in the transgenic lines. The integrated evaluation index provided an adequate, quantitative assessment of salt tolerance of potato and can be used effectively in the development of salt‐tolerant cultivars.